2017
DOI: 10.21037/qims.2017.10.08
|View full text |Cite
|
Sign up to set email alerts
|

The novel targets of DL-3-n-butylphthalide predicted by similarity ensemble approach in combination with molecular docking study

Abstract: Background: DL-3-n-butylphthalide (NBP) is a drug for treating acute ischemic stroke, and may play a neuroprotective role by acting on multiple active targets. The aim of this study was to predict the target proteins of NBP in mammalian cells. Methods:The similarity ensemble approach search tool (SEArch), one of the commonly used public bioinformatics tools for target prediction, was employed in the experiment. The molecular docking of NBP to target proteins was performed by using the three-dimensional (3-D) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…A large number of experiments at home and abroad have revealed that NBP can regulate brain energy metabolism (Yan, Wang, Yao, Liu, & Xiao, ), protect the mitochondria (Min et al, ), promote normal blood flow in the ischemic area (Xu et al, ), inhibit oxidative stress and platelet aggregation (Li et al, ; Zhao, Li, Zhang, Chen, & Li, ), and prevent the vigorous apoptosis of cells (Min et al, ). In addition, Chinese scholars found that NBP plays a neuroprotective role by acting on multiple active targets (Wang et al, ; Zhao et al, ). Furthermore, some scholars considered that the effective rate of NBP in treating ACI can reach 76%–93% (Offner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of experiments at home and abroad have revealed that NBP can regulate brain energy metabolism (Yan, Wang, Yao, Liu, & Xiao, ), protect the mitochondria (Min et al, ), promote normal blood flow in the ischemic area (Xu et al, ), inhibit oxidative stress and platelet aggregation (Li et al, ; Zhao, Li, Zhang, Chen, & Li, ), and prevent the vigorous apoptosis of cells (Min et al, ). In addition, Chinese scholars found that NBP plays a neuroprotective role by acting on multiple active targets (Wang et al, ; Zhao et al, ). Furthermore, some scholars considered that the effective rate of NBP in treating ACI can reach 76%–93% (Offner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nie et al [60], Bai et al [61], Cai et al [62,63] adopted graph Laplacian matrix to keep the graph’s local structure. Moreover, the Studies [34,6467] revealed that the combination of multiple similarities helps to improve performances. Inspired by pioneer work, we define a novel ensemble graph Laplacian regularization: where D i is a diagonal matrix whose diagonal elements are corresponding row sums of W i , and θ = [ θ 1 , θ 2 ,⋯, θ i ,⋯, θ m ] is a weight vector which is introduced to control the contribution of different graph Laplacian regularizations, and tr (∙) is the trace of a matrix.…”
Section: Methodsmentioning
confidence: 99%
“…Focusing proteins in drug discovery direct the way to finding the best lead compound, with high efficacy at the lowest micromolar concentrations. Numerous software tools for protein-ligand dockings, such as Autodock, DOCK 4.0, GOLD, Flex-X, ICM, SLIDE, GLIDE, and DeepBindRG, were developed based on various scoring functions, including empirical, knowledge-based, and machine learning, and are summarized in Table 2 [50,[115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130]. The field of drug designing has been rapidly advancing in recent decades, and many new state-of-the-art technologies and methods have been discovered [20,[104][105][106][107][108][109][110][111][112][113][114].…”
Section: Challenges and Opportunities In Targeting Ctdsp1mentioning
confidence: 99%